PENAMPUNGAN KUCING (CAT SHELTER) DI BANJARBARU - Diyanti, Tria; Oktaviana, Anna (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2020)
Caring for pets has become a part of the lifestyle of today's modern society. However, the high interest in raising animals is also accompanied by the growth of abandoned animal populations in the city of Banjarbaru due to neglect from non-committed owners. As a respond to this problem, a shelter facility emerged for abandoned animals who were sick, injured, tortured, or needed a protection. The design of Cat Shelter in Banjarbaru is a facility that seeks to meet the physical and psychological needs of animals but also still considers the sustainability of facilities by implementing an environmentally friendly design approach. Using Sustainable Architecture concepts as a solution to problems with strategies for considering land use, community, health and well-being, as well as the efficiency of materials, energy and water, then formed a design of green buildings and healthy, which is beneficial for residents of shelter facilities.